Study of an intelligent and multicriteria scheduling service, using academic benchmarks. Issue 11 (1st November 2016) - Ounnar, Fouzia; Pujo, Patrick; Hachicha, Maroua; Dubromelle, Yves
Abstract : The implementation of new production organisation methods becomes essential in the context of the evolution of companies. These methods include scheduling, which, in this context, is generally based on multiple criteria. Multicriteria optimisation methods are needed to search all optimal solutions and multicriteria decision-making methods are needed to choose the best compromise between potential solutions. The objective here is to evaluate the performance of a multicriteria decision-making method used to establish a real-time scheduling, in the holonic, isoarchic and multicriteria model, named the Product, Resource, Order, Simulation, Isoarchic System (PROSIS), through academic benchmarks. After presenting the existing intelligent control based on an intelligent scheduling service, the choice of the multicriteria aid method named the analytic hierarchy process is justified. Following this, the implementation of the multicriteria scheduling service in PROSIS is described. Finally, the benchmarks allowing to study the performance of the multicriteria scheduling are presented before analysing the results.